Post‐liver transplantation chronic kidney disease is associated with increased cardiovascular disease risk and poor survival. (23rd November 2021) - Bhanji, Rahima A.; Chow, Jessica; Ma, Mang; Pannu, Neesh; Bain, Vincent G.; Kneteman, Norman; Montano‐Loza, Aldo J.
Summary: Chronic kidney disease (CKD) is common following liver transplantation (LT). We aimed to investigate the frequency, risk factors, and impact of CKD on cardiovascular disease (CVD), graft, and patient survival. We analyzed 752 patients who received LT at the University of Alberta. Development of CKD was defined as eGFR <60 ml/min for greater than 3 months, intrinsic renal disease or presence of end‐stage renal disease requiring renal replacement therapy. 240 patients were female (32%), and mean age at LT was 53 ± 11 years. CKD was diagnosed in 448 (60%) patients. On multivariable analysis, age (OR 1.3; P  = 0.01), female sex (OR 3.3; P  < 0.001), baseline eGFR (OR 0.83; P  < 0.001), MELD (OR 1.03; P  = 0.01), de novo metabolic syndrome (OR 2.3; P  = 0.001), and acute kidney injury (OR 3.5; P  < 0.001) were associated with CKD. A higher tacrolimus concentration to dose ratio was protective for CKD (OR 0.69; P  < 0.001). CKD was associated with post‐transplant CVD (26% vs. 16% P  < 0.001), reduced graft (HR 1.4; P  = 0.02), and patient survival (HR 1.3; P  = 0.03). CKD is a frequent complication following LT and is associated with an increased risk of CVD and reduced graft and patient survival. Abstract : Chronic kidney disease (CKD) is common following liver transplantation. We investigated risk factors, and impact of CKD on cardiovascular disease (CVD), graft/patient survival. A higher tacrolimus concentration to dose ratio was protective for CKD (OR 0.69). CKD led to increased post‐transplant CVD (26% vs. 16%), and reduced graft/patient survival.